Perencanaan Pembelajaran Pada Mata Pelajaran Sejarah Di SMA Negeri 4 Kabupaten Tangerang - Dita Primaisela Arinda; Aulia Zahra Yuanita; Santi Dame Mawarni; Ilham An’nur Pajar; Osep Ismana; Ana Nurhasanah (PT. ALHAFI BERKAH INDONESIA, 2024)
This article aims to find out how the learning planning process for history subjects is realized at SMA Negeri 4 Tangerang Regency, Banten Province. The method used in writing this article is a descriptive qualitative approach. Data collection was carried out by observing schools, conducting interviews with informants related to the focus, and documenting supporting matters in this article. The results and discussion obtained are: First, what are the considerations in preparing learning plans, as well as why teachers need to prepare learning plans, and the teacher's goals in preparing learning plans. Second, how is the curriculum analysis in educational level units at SMA Negeri 4 Tangerang Regency. Third, how to choose the right learning method approach according to the learning objectives. Fourth, how to develop teaching materials, learning media, LKPD, and learning evaluation instruments. Fifth, the obstacles that teachers face in preparing learning plans. Sixth, how does the teacher carry out solutions for corrective action for learning planning